Interpretasi Konstitusional Independensi KPK menurut UU No. 19 Tahun 2019 Tentang KPK Perspektif Siyāsah Dustūriyyah - Ritonga, Nazwa Fadillah; Khalid (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
The amendment to Law Number 19 of 2019 concerning the Corruption Eradication Commission (KPK) has generated constitutional debate regarding the institutional position and independence of the KPK. Although Article 3 of the Law explicitly states that the KPK is an independent institution, it simultaneously places the KPK within the executive branch, giving rise to differing interpretations concerning the consistency of its institutional status and the implementation of its authority. This study aims to analyze the constitutional interpretation of the KPK’s independence under Law Number 19 of 2019, examine the recruitment mechanism of KPK leaders in maintaining institutional independence, and assess the concept of KPK independence from the perspective of Siyāsah dustūriyyah. This research employs normative juridical legal research using statutory, conceptual, and case approaches. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed qualitatively through content analysis. The findings indicate that the placement of the KPK within the executive branch creates legal ambiguity regarding its institutional independence. Furthermore, although the recruitment mechanism of KPK leaders formally involves a selection process, presidential nomination, and approval by the House of Representatives, the involvement of political institutions potentially affects public perceptions of the KPK's independence. From the perspective of Siyāsah dustūriyyah, institutional independence reflects the principles of trustworthiness (amanah), justice ('adl), and public welfare (maslahah), which are essential foundations for ensuring impartial and accountable law enforcement